A Day-End Transaction Price Anomaly - Harris, Lawrence (Journal of Financial and Quantitative Analysis, 1989)
A large mean price change is observed on the last daily NYSE transaction. This suggests that closing prices may not consistently represent stock values. Transaction prices are studied to further characterize the day-end price rise and to determine whether it is due to any limited subsample of stocks or dates. The results indicate that the phenomenon is pervasive over most firms and days. Some evidence suggests that it is caused by a change in the frequency of ask prices at day-end.